CompTIA Cloud Essentials+ Certification Study Guide, Second Edition (Exam CLO-002), 2nd Edition - Lachance, Daniel (McGraw-Hill, 2020)
Publisher's Note: Products purchased from Third Party sellers are not guaranteed by the publisher for quality, authenticity, or access to any online entitlements included with the product. The best IT certification exam study system available Filled with hands-on exercises and practice exam questions, CompTIA Cloud Essentials+"!Certification Study Guide, Second Edition (Exam CLO-002) covers what you need to know-and shows you how to prepare-for this challenging exam." 100% complete coverage of all official objectives for exam CLO-002 " Exam Readiness checklist-you're ready for the exam when all objectives on the list are checked off " Exam Watch notes call attention to information about, and potential pitfalls in, the exam " Two-Minute Drills for quick review at the end of every chapter " Simulated exam questions match the format, tone, topics, and difficulty of the real exam Covers all the exam topics, including: The Principles of Cloud Computing " The Business Side of Cloud Computing " Cloud Planning " Compliance and the Cloud " Cloud Storage Infrastructure " Cloud Network Infrastructure " Cloud Compute Infrastructure " Applications and Big Data in the Cloud " Cloud DevOps " Security and the Cloud " Managing Cloud Risk Online content includes: " Test engine that provides full-length practice exams and customized quizzes by chapter or by exam domain " Access to entire book PDF